Implementation and Strategies Differentiated Learning for Arabic Language Learning at Islamic High School - Yahya, Amri; Ahsanuddin, Mohammad; Irhamni; Syukur, Hasan; Iman, Muhammad Nur (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The Merdeka Curriculum encourages a more adaptive and learner-centered learning approach, one of which is through differentiated learning. This approach is important in learning Arabic which requires mastery of complex skills such as listening, speaking, reading and writing. This study investigates the implementation of differentiated instruction within the Merdeka Curriculum at Islamic high school Darul Faqih Malang, with a focus on examining the instructional strategies employed by teachers, as well as identifying the opportunities and challenges encountered in practice. Utilizing a qualitative descriptive methodology, With case study research type. Data were collected through classroom observations, in-depth interviews with Arabic language teachers, and analysis of instructional documents. The data were then analyzed using the Miles and Huberman model. The findings reveal that instructional planning is conducted systematically, guided by the formulation of learning outcomes, learning objective pathways, and the use of contextual and adaptable teaching modules. Instructional delivery is tailored through student grouping based on learning preferences, the application of active learning strategies such as discussion and problem-based learning, and the integration of Pancasila student profile values. Teachers’ strategies encompass diagnostic assessment, peer tutoring, the use of varied instructional media and methods, and intensive mentoring. Despite challenges related to students’ diverse backgrounds, motivation levels, and infrastructural limitations, differentiated instruction fosters an inclusive, collaborative, and transformative learning environment. This study contributes valuable insights into the practical effectiveness of differentiated instruction in Arabic language education under the Merdeka Curriculum framework. This study provides scientific contributions for Arabic language teachers who will implement differentiated learning, especially Arabic language learning.